MEMAHAMI NASIKH DAN MANSUKH DALAM HADITS - Muhammad Agorrul Kirom; Durrotul Iqomatin Ni’mah (AL-BAYAN INSTITUTE, 2025)
Nasikh and mansukh are important concepts in the study of hadith and the Qur'an, relating to the abolition or replacement of sharia law by later evidence. Understanding these concepts is a primary requirement for a mujtahid in establishing Islamic law. Nasikh means evidence that abolishes, while mansukh is evidence that is abolished. This study aims to understand the concepts of nasikh and mansukh in hadith and how scholars interpret them in the context of Islamic law. Using qualitative methods and a library study approach, this study analyzes the contents of various classical and contemporary literature, such as hadith books and ushul fiqh (Islamic jurisprudence) that discuss the abolition of laws in the Sunnah of the Prophet Muhammad (peace be upon him). The research design used is content analysis, which allows researchers to systematically examine their meaning, types, and conditions. Data were collected through literature documentation, then analyzed through a process of reduction, classification, interpretation, and conclusion. The results show that there are three types of naskh: abolishing a word without abolishing a law, abolishing a law without abolishing a word, and abolishing both simultaneously. The discussion covers the requirements for a naskh, the differences of opinion between classical and contemporary scholars regarding the validity of a naskh, and the classification of the relationship between the Qur'an and hadith within the context of naskh. Naskh is seen as a form of adaptation of Islamic law to the dynamics of society, safeguarding the public interest, and demonstrating the flexibility of sharia in responding to changing times. Understanding nasikh and mansukh in hadith is not only within the context of Islamic law but also reflects the dynamics of the scholars' ijtihad in response to social developments and the needs of the community